Structural Complexity of the Cerebellum and Cerebral Cortex is Reduced in Spinocerebellar Ataxia Type 2. Issue 6 (5th July 2018) - Marzi, Chiara; Ciulli, Stefano; Giannelli, Marco; Ginestroni, Andrea; Tessa, Carlo; Mascalchi, Mario; Diciotti, Stefano
ABSTRACT: BACKGROUND AND PURPOSE: Fractal dimension (FD) is an index of structural complexity of cortical gray matter (GM) and white matter (WM). Application of FD to pontocerebellar degeneration has revealed cerebellar changes. However, so far, possible concurrent cerebral changes and progression of changes in brain complexity have not been investigated. METHODS: We computed FD of cerebellar and cerebral cortex and WM derived from longitudinal brain MRI of patients with spinocerebellar ataxia type 2 (SCA2), which is an inherited cause of pontocerebellar degeneration. Nine SCA2 patients and 16 age‐matched healthy controls were examined twice (3.6 ± .7 and 3.3 ± 1.0 years apart, respectively) on the same 1.5T MR scanner with T1‐weighted imaging. Cortical GM and WM of the cerebrum and cerebellum were segmented using FreeSurfer and FD of these segmentations were computed. RESULTS: At baseline, FD values of cerebellar GM and WM were significantly ( P < .001) lower in SCA2 patients (2.48 ± .04 for GM and 1.74 ± .09 for WM) than in controls (2.56 ± .02 for GM and 2.22 ± .19 for WM). Also, FD values of cerebral GM were significantly ( P < .05) lower in SCA2 patients (2.39 ± .03) than in controls (2.43 ± .02). No significant differences were observed for FD of the cerebral WM. The rate of change of FD values was not significantly different between SCA2 patients and controls. CONCLUSIONS: The structural complexity of the cerebellum and cerebral cortex is reduced in SCA2 patients. Fractal analysis seems not to be able to demonstrate progression of changes associated with degeneration in SCA2.